Common musculoskeletal problems a handbook - Daniels, James M.; Hoffman, M. Rebecca (Mary Rebecca) (Springer, 2010)
Common Musculoskeletal Problems in Primary Care: A Handbook is an excellent point of care resource for health care providers to better diagnose and treat patients presenting with common musculoskeletal complaints. Each chapter in this book focuses on a specific joint or region and discusses anatomy, red flags, approach to the patient, common clinical presentations and management, and includes a flow diagram to help direct management and follow-up of a patient?s problem. A user-friendly approach makes this handbook an ideal reference for medical students, primary care residents, and practicing primary care providers alike.